THE SHIFT TOWARDS DIGITAL LEADERSHIP AS A STRATEGIC OPTION TO ENHANCE DIGITAL MATURITY AT OOREDOO ALGERIA: A STUDY BASED ON THE WESTERMAN MATRIX AND COLLEAGUES - Belmir Sara,; Saadi Wahida, (International Journal of Innovative Technologies in Social Science, 2024)
Digital leadership plays a vital role in enhancing digital maturity in the business sector in Algeria by relying on digital technologies and adopting electronic communication methods within its institutions, especially economic ones. This approach raises the level of digital maturity by increasing operational efficiency and improving productivity, enabling them to reach new markets and expand their business through e-commerce and online marketing. Additionally, digital leadership enhances communication and collaboration within the organization, contributing to better information management and increasing data availability for improved decision-making. Moreover, digital technologies can also bolster research and development processes and encourage innovation in Algerian companies, leading to greater success and increased competitiveness on both national and international levels. This study employs a case study methodology, deemed most suitable for the research topic. Semi-structured interviews and the Westerman Matrix were selected to analyze the digital maturity level in some branches of Ooredoo in eastern Algeria, which were chosen as the focus of our study. The results indicate that Ooredoo does not possess a high level of digital maturity, despite having transformative digital leaders. However, it needs to optimally utilize the available technology to develop work methods and create differentiation and added value. Therefore, enhancing its digital maturity requires supporting digital leadership values of participation and collaboration with employees to create an organizational environment that promotes digital transformation goals and encourages the acceptance of change as part of the organizational culture by adopting modern technologies and striving to master them.